2012
DOI: 10.4103/0253-7613.93848
|View full text |Cite
|
Sign up to set email alerts
|

Molecular docking and ex vivo pharmacological evaluation of constituents of the leaves of Cleistanthus collinus (Roxb.) (Euphorbiaceae)

Abstract: Objective:To investigate the involvement of alpha adrenergic receptors in hypotension induced by cleistanthin A and cleistanthin B.Materials and Methods:Cleistanthins A and B were isolated from the leaves of Cleistanthus collinus using a column chromatographic method and purified. Structures were confirmed by spectroscopic analysis. The compounds were prepared for molecular docking studies using Ligprep 2.3 module and Induced Fit Docking was carried out against α-1 adrenergic receptors using Glide. The ex vivo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 15 publications
0
9
0
Order By: Relevance
“…The molecular docking studies showed that cleistanthins A and B had a significant alpha-adrenergic receptor interaction similar to prazosin. [ 29 ] It was reported that cleistanthins A and B blocked alpha-adrenergic receptor in guinea pig vas deferens. [ 24 ] The present study also picked up similar effect as evident from the failure to record a rise in the mean arterial pressure after the administration of the catecholamines in the cleistanthin treated rats indicating the alpha-adrenergic receptor blocking property of the latter [ Figure 1 ].…”
Section: Discussionmentioning
confidence: 99%
“…The molecular docking studies showed that cleistanthins A and B had a significant alpha-adrenergic receptor interaction similar to prazosin. [ 29 ] It was reported that cleistanthins A and B blocked alpha-adrenergic receptor in guinea pig vas deferens. [ 24 ] The present study also picked up similar effect as evident from the failure to record a rise in the mean arterial pressure after the administration of the catecholamines in the cleistanthin treated rats indicating the alpha-adrenergic receptor blocking property of the latter [ Figure 1 ].…”
Section: Discussionmentioning
confidence: 99%
“…Cleistanthin B was isolated from the leaves of C. collinus (Euphorbiaceae) as described in our previous study. 15 Taxonomically identified plant leaves were collected in the regions of Pondicherry district and it was certified by Botanical survey of India, Coimbatore (BSI/SC/5/23/08-09/Tech.241).…”
Section: Methodsmentioning
confidence: 99%
“…The natural compounds of cleistanthins A and B were isolated and purified from the leaves of Cleistanthus collinus using column chromatographic method and the structures were determined. [ 4 ] These structures [ Figure 1 ] were built using builder panel in Maestro and ligand preparation was carried out for these compounds by Ligprep 2.3 module (Schrödinger, USA, 2009). Ligprep performs addition of hydrogens, 2D to 3D conversion, realistic bond lengths and bond angles, low energy structure with correct chiralities, ionization states, tautomers, stereochemistries and ring conformations.…”
Section: Methodsmentioning
confidence: 99%
“…Both compounds had significant antineoplastic and hypotensive effects in rodents and its cell lines. [ 4 5 ] The in vitro studies of cleistanthins A and B compounds showed a significant diuretic effect but the effect was not comparable with standard diuretic agents. [ 4 ] Hence; the present study aims to determine the possible interactions and binding free energy of cleistanthins A and B with target of ACE-I using Induced Fit Docking and Prime Molecular Mechanics Generalized Born Surface Area (MM-GBSA) analysis.…”
Section: Introductionmentioning
confidence: 99%